2021
DOI: 10.1172/jci.insight.135626
|View full text |Cite
|
Sign up to set email alerts
|

Discordant hepatic fatty acid oxidation and triglyceride hydrolysis leads to liver disease

Abstract: To extract energy from stored lipids, fatty acids must first be liberated from triglyceride before their β-oxidation in mitochondria in a coordinated and stepwise manner. To determine the independent and interdependent roles of hepatic triglyceride hydrolysis and fatty acid oxidation, mice were generated with a liver-specific defect in triglyceride hydrolysis (Atgl L–/– ), fatty acid oxidation (Cpt2 L–/– ), or both (double knockout). The loss of either gene resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…The increased expression of markers of gluconeogenesis observed in the present study is more likely due to increased mitochondrial metabolism, as previous studies demonstrate that induction of lipid oxidation is required for the endergonic steps of gluconeogenesis. In the case of an increased systemic energy demand, i.e., during exercise, both processes, fatty acid oxidation and gluconeogenesis, are constitutively activated [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…The increased expression of markers of gluconeogenesis observed in the present study is more likely due to increased mitochondrial metabolism, as previous studies demonstrate that induction of lipid oxidation is required for the endergonic steps of gluconeogenesis. In the case of an increased systemic energy demand, i.e., during exercise, both processes, fatty acid oxidation and gluconeogenesis, are constitutively activated [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that adipocyte ATGL-dependent lipolysis is required for fasting-induced PPARα-dependent hepatic gene expression, and that together they orchestrate the fasting response in the liver. Interestingly, a recent study, using liver-specific deletion of Atgl in mice, has reported that hepatic ATGL is not required for the fasting-induced PPARα-dependent responses in the liver, suggesting that adipocyte lipolysis-derived fatty acids are sufficient to activate PPARα independent of the hepatocyte lipolysis [35].…”
Section: Discussionmentioning
confidence: 99%
“…This ultimately requires tight coordination between the hepatocyte’s metabolic state, genome architecture, and transcriptional output. Fasting Cpt2 L−/− mice prompts accumulation of fatty acids, including putative endogenous Pparα ligands (Lee et al, 2016; Selen et al, 2021). Using this mouse genetic model and a combination of next-generation sequencing platforms we clarify the role for hepatic lipid content in metabolic gene transcription, and in particular how Pparα, activated by natural ligands, maintains the transcriptional architecture necessary for target gene expression ( Fig.…”
Section: Discussionmentioning
confidence: 99%